Un antropólogo en el aula: ¿Por qué los estudiantes se portan mal? - Mejía Carrión, Wilmer (2018)
Student misconduct is a common and constant problem; it seems to be an endemic trouble that seems to have no end. The solution of the problem has been entrusted to a psychologist, considering that the discipline of psychology has the solution to this problem. Thus, it is considered that the - bad or good - behaviors within the classroom do not compete with anyone else than this discipline. What could anthropologists do then in the classroom rather than just teach some courses of letters? In this paper I realize the conclusions that an anthropologist makes from a field work in several private schools. Giving a different perspective about school behavior given by other disciplines. Power relations and culture will be seen within the school institution and how these affect the various social actors operating in it.